Retrospective, multicenter evaluation of complications in the treatment of diaphyseal femur fractures in pediatric patients. (October 2019) - Memeo, A.; Panuccio, E.; D'Amato, R.D.; Colombo, M.; Boero, S.; Andreacchio, A.; Origo, C.; Pedretti, L.
Abstract: Introduction: Femoral shaft fractures are the commonest major pediatric fractures. For generations, traction and casting were the standard method of treatment for children. However, over the past two decades there has been growing recognition of the advantages of fixation and rapid mobilization. Methods: A prospective multicenter study was conducted at four Italian centers of reference for pediatric fractures (January 2005 to December 2014). The study involved 62 patients of both sexes, between 6 and 14 years of age, with closed femoral shaft fractures. The aim was to find out more about the short-term complications of titanium elastic nailing in diaphyseal femur fractures in children in order to reduce them. Results: The commonest complication observed in our study was pain at the nail entry point (24.19%) due to a local inflammatory reaction. After 1 year, 3.22% had limbs of different lengths. Proximal migration occurred in 1.61% of cases. Discussion: Over the last two decades, the treatment of femoral shaft fractures in pediatric patients has developed to include internal fixation using Titanium Elastic Nails (TEN). We only observed a few complications in our study, most of which were minor and associated with the surgical technique employed, particularly during the initial phase of the surgeon's learning curve. Conclusions: TEN are an excellent internal fixation system if used by an expert surgeon and have a very low rate of complications. None of them produced permanent damage in the patients. In older children weighing more than 50 kg, alternative techniques such as subtrochanteric nailing, plates, or external fixation are advisable.